Electronics for kids for dummies - Shamieh, Cathleen (John Wiley &​ Sons, Inc., 2016)
ELECTRONICS ENGINEERING. The easy way for kids to get started with electronics If your youngster likes to tinker, Electronics For Kids For Dummies is here to teach them the core concepts of electronics in a fun and engaging way. Written in a language elementary-to-middle-school-aged kids can understand, it's packed with full-color photos, easy-to-follow instructions, simple examples, and 13 cool projects that will boost your child's confidence while instilling valuable electronics lessons. Written by an experienced engineer who authored Electronics For Dummies, this friendly guide shows children the right way to learn about this exciting but potentially dangerous field.